Factors associated with information and communication technology (ICT) applications in decision making - Mohamed Yusof, Noreha; Chooi, Leng Ang (2004)
The rapid and pervasive growth of Information and Communication Technology (ICT) has forced organizations worldwide to re-examine the role of ICT in supporting their business goals.The aim of this study was to determine factors associated with the use of ICT in decision making among the listed organizations on Kuala Lumpur Stock Exchange (KLSE). Three categories of contextual factors, namely organizational, technical and process were examined to determine if their affect ICT applications in decision making. The results revealed that process factors, specifically data support was associated with the use of ICT even through support from top management, incentive from the government, team working and friendly output formats were perceived to help promote the use of ICT in decision making among the responding organizations.